Design of a Portable Power Supply with Real-Time Monitoring Using KL Series Battery Monitor (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
The demand for portable and environmentally friendly power supply systems is increasing due to the growing need for efficient and sustainable energy usage. Most of the existing power supply systems lack comprehensive real-time monitoring of electrical parameters such as voltage, current, and actual power consumption. This study aims to design a portable power supply prototype capable of powering DC devices while monitoring power usage in real time using the KL Series Battery Monitor. The methodology includes technical design and experimental testing to evaluate energy efficiency under actual loads. The prototype incorporates five core elements: a rechargeable system, electronic circuit breaker (BMS), automatic blower, green materials, and a LiFePO₄ based energy storage unit. Performance evaluation was conducted through load testing with various DC devices including a stand fan, LED lamp, light bulb, and phone charger. Findings show efficiency instability during initial use and high-startup load. However, real-time voltage-current monitoring and proper thermal design help reduce negative effects. The system's average power efficiency is approximately 89.4%, indicating stable performance for medium-duration applications. The findings confirm that the prototype meets its intended objectives in terms of energy efficiency, safety, and environmental sustainability. This solution demonstrates strong potential for use in off-grid applications, green education tools, and portable power systems in various community settings.